Prevalence of Fabry disease in male patients with unexplained left ventricular hypertrophy in primary cardiology practice: prospective Fabry cardiomyopathy screening study (FACSS). Issue 3 (31st October 2013) - Palecek, Tomas; Honzikova, Jitka; Poupetova, Helena; Vlaskova, Hana; Kuchynka, Petr; Golan, Lubor; Magage, Sudheera; Linhart, Ales
Abstract: Background: A number of studies have already investigated the prevalence of Fabry disease (FD) in adult patients with unexplained left ventricular hypertrophy (LVH) with rates varying from 0 % up to 12 % reflecting referral and gender bias as well as differences in diagnostic methodology. We aimed to perform a prospective screening study evaluating the prevalence of FD in male patients older than 30 years with strictly defined unexplained LVH followed by general cardiologists. Methods: A predefined number of 100 men with unexplained LVH, defined as maximal wall thickness ≥ 13 mm, were identified during an echocardiographic examination in primary cardiology practice and screened by assessing α‐galactosidase A activity in dried blood spots (DBS) or in plasma. Results: Four men (52 ± 4 years, maximal LV wall thickness 18 ± 3 mm) were diagnosed with FD confirmed by enzyme analysis in leukocytes as well as by genetic analysis. Mild extracardiac manifestations of FD were present in two of them. Conclusions: The prevalence of FD in our cohort of male patients followed in primary cardiology practice with strictly defined otherwise unexplained LVH was 4 %. We recommend systematic screening for FD in all men older than 30 years with LVH of unknown etiology even in the absence of obvious extracardiac manifestations of FD.